XALQI UZAQ ÓMIR KÓRIWSHI MÁMLEKETLERGE ILIMIY SÍPATLAMA - Utepova, G.B. (SCIENCE and SOCIETY, 2024)
This article is aimed at a comparative assessment from a scientific perspective of the possibilities and causes of longevity among people living in different countries.